Control of Surface Plasmon Resonance in Silver Nanocubes by CEP-Locked Laser Pulse - Ju Liu; Zhiyuan Li (Photonics, 2022)
Localized surface plasmon resonance (LSPR) of metal nanoparticles has attracted increasing attention in surface-enhanced Raman scattering, chemical and biological sensing applications. In this article, we calculate the optical extinction spectra of a silver nanocube driven by an ultrashort carrier envelope phase (CEP)-locked laser pulse. Five LSPR modes are clearly excited in the optical spectra. We analyze the physical origin of each mode from the charge distribution on different parts of the cubic particle and the dipole and quadrupole excitation features at the LSPR peaks. The charge distribution follows a simple rule that when the charge concentrates from the face to the corners of the cubic particle, the resonant wavelength red-shifts. Then we modulate the LSPR spectra by changing CEP. The results show that CEP has selective plasmon mode excitation functionality and can act as a novel modulation role on LSPR modes. Our work suggests a novel means to regulate LSPR modes and the corresponding optical properties of metal nanoparticles via various freedoms of controlled optical field, which can be useful for optimized applications in chemical and biological sensors, single molecule detection, and so on.